Metaphor, Paradigm, and Education - Ivie, Stanley (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 2017)
Metaphor is a critical tool for thought. Lying at the heart of every systematic body of knowledge are three root metaphors — mechanism, organism, and mind. Historically, schools of philosophy — realism, naturalism, and idealism — have grown up around these metaphors. The root metaphors and their corresponding philosophies provide the paradigms underlying different exemplars of education. To illustrate how metaphors, paradigms, and exemplars all shape educational thought, the works of three educators — Hunter, Piaget, and Bruner — have been selected.